The importance of the assistive digital technologies associated from the english teacher’s work with students targeted to special education (Research, Society and Development, 2022)
The main objective of this word is to present a reflection about the use of Assistive Technologies (TA) as a support tool for the work of the English language teacher who has in his classroom students who are the target audience of Special Education. In view of this, an analysis of the Assistive Technologies used by teachers in this area was carried out as well as a survey of the technologies that are available to contribute to the work of the English language teacher with students who are the target audience of Special Education. The methodology of this work, in turn was based on a qualitative approach and was based on studies of theoretical references of authors such as Martha Gabriel among others. That said, the investigation made it possible to know the scenario of research on Assistive Technologies and the positive results of the uses of this technology in terms of improving the quality of life of students with special needs, that is target public students of Special education.